Kemas Ulang Informasi Pepatah-Petitih Minangkabau dalam Bentuk E-Book - Oktavia, Reno; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractÂ This paper discusses the information down the proverbial-Minangkabau petitih in the form of E-book. The purpose of this paper is to describe the repackaging information adage-petitih Minangkabau. The method used is descriptive research methods by collecting data through observation conducted in communities in Nagari Batipo, Tanah Datar Regency.On the basis of the discussion it was concluded that the stages of manufacture down the proverbial information-petitih Minangkabau, as follows: 1) Select and designate topics; 2) Determine strategy in seeking information; 3) determine the location of information and how to access; 4) use information by way of evaluating; 5) Package information; 6) product and process Evaluation pembuatannyadengan way: a) the making of the cover; b) Foreword; c) table of contents; d gist discussion); e) cover.Keywords: adage-petitih, packaging information, Minangkabau